2021
DOI: 10.1515/hsz-2021-0259
|View full text |Cite
|
Sign up to set email alerts
|

The antioxidant Rutin counteracts the pathological impact of α-synuclein on the enteric nervous system in vitro

Abstract: Motoric disturbances in Parkinson’s disease (PD) derive from the loss of dopaminergic neurons in the substantia nigra. Intestinal dysfunctions often appear long before manifestation of neuronal symptoms, suggesting a strong correlation between gut and brain in PD. Oxidative stress is a key player in neurodegeneration causing neuronal cell death. Using natural antioxidative flavonoids like Rutin, might provide intervening strategies to improve PD pathogenesis. To explore the potential effects of micro (mRutin) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 108 publications
0
6
0
Order By: Relevance
“…41 Rutin has recently been identified as a potential neuroprotective compound in an A53T α-synuclein in vitro neurotoxicity model in enteric neurons. 42 Quercetin, in combination with piperine, has also recently been shown to attenuate the motor deficits as well as molecular changes in a rotenone- and iron deficiency-based rat PD model, 43 while in a 6-OHDA-based rat model quercetin itself was found to increase antioxidant enzymes and protected against PD. 44 Since many polyphenols, including quercetin and rutin, are antioxidants, their effect on relieving oxidative stress was proposed to be critical in neuroprotection in various in vivo and in vitro PD models as well as for other neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…41 Rutin has recently been identified as a potential neuroprotective compound in an A53T α-synuclein in vitro neurotoxicity model in enteric neurons. 42 Quercetin, in combination with piperine, has also recently been shown to attenuate the motor deficits as well as molecular changes in a rotenone- and iron deficiency-based rat PD model, 43 while in a 6-OHDA-based rat model quercetin itself was found to increase antioxidant enzymes and protected against PD. 44 Since many polyphenols, including quercetin and rutin, are antioxidants, their effect on relieving oxidative stress was proposed to be critical in neuroprotection in various in vivo and in vitro PD models as well as for other neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids are divided into six main subclasses (flavones, Flavonols, flavanones, flavanols, isoflavones, and anthocyanins). Studies have shown that flavonoids such as baicalein, quercetin, and rutin [ 136 , 137 , 138 ] can have several positive health effects, including a decreased risk of PD, despite their limited bioavailability. Their physiological actions, which include antioxidative, anti-inflammatory, anti-apoptotic, and lipid-lowering qualities, are the reason for this.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Pro-inflammatory cytokine levels decreased as a result of the senolytic therapy, which may partly be attributable to the elimination of oligodendrocyte progenitor cells (OPCs) with the Senescence-Associated Secretory Phenotype (SASP) [ 140 ]. The potential beneficial effect of flavonoids in the brain appears to be linked to their ability to interact with glial signaling and intracellular neuronal pathways, triggering neuronal regeneration, increasing existing neuronal functions, protecting vulnerable neurons, or influencing the cerebrovascular and peripheral system [ 136 , 137 , 138 , 141 ]. Acetylcholine (ACh) is the most versatile neurotransmitter that plays its role in transmission of impulse across different neurotransmitters.…”
Section: Flavonoidsmentioning
confidence: 99%
“…In recent years, there has been increasing interest in the function and action of antioxidants in various pathologies, and even the possible mechanisms of action are beginning to be elucidated. Figure 1 shows some antioxidants and their effects mainly in the ENS and CNS [21][22][23][24][25][26] (Figure 1).…”
Section: Relationship Of the Enteric System With Oxidative Stress-ant...mentioning
confidence: 99%